Environmental Management Based on Islamic Sharia and Customary Law in Aceh - zahratul idami; Israr Hirdayadi; Qudwatin Nisak M Isa; Alfi Rahman (Universitas Lampung, 2022)
This paper discuss how Islamic and customary laws regulate environmental management in Aceh. A qualitative approach was used by implementing a normative juridical method. First, the data from various literature or references and documents were gathered related to the topic. It was then qualitatively analysed using the concept, constitutional and historical approaches, and Islamic environmental management regulations. According to the study's findings, the Islamic Shari'a and Aceh Customary Law cannot be separated, citing the hadith Maja